Building Vocabulary in Primary School Students Using Contextual Teaching Learning Model - Azzahra, Shintia; Kaniadewi, Nita (Cokroaminoto Journal of Primary Education, 2025)
This study explores the effectiveness of the Contextual Teaching and Learning (CTL) model supported by digital media to improve English vocabulary acquisition among fifth-grade students at SD Negeri Serpong 01. The research followed a Classroom Action Research (CAR) design, carried out in two cycles during the second semester of the 2024/2025 academic year. A total of 25 fifth-grade students took part in the study as the research subjects. The CTL approach was applied through storytelling, role-playing, and problem-solving activities, enhanced by digital tools such as videos and interactive quizzes. To gather insights, the researcher used classroom observations, student work samples, field notes, and interviews. The data were then analyzed using qualitative descriptive methods. The success indicators were set as 75% of students mastering 80% of the target vocabulary. The findings revealed notable gains in vocabulary retention, along with increased student motivation and more active participation in class. The classroom became more inclusive and student-centered, helping learners relate new words to everyday contexts. Although challenges like time constraints and differences in students’ digital literacy were encountered, the combination of CTL and digital tools proved effective in supporting vocabulary learning aligned with the Kurikulum Merdeka. This approach also reflects the broader goals of 21st-century education, encouraging critical thinking, creativity, collaboration, and digital literacy among young learners